Characterization of the binding features between SARS-CoV-2 5’-proximal transcripts of genomic RNA and nucleocapsid proteins - Shih-Cheng Chen; Cui-Ting Xu; Chuan-Fu Chang; Chia-Shin Yang; Pin-Han Lin; Wei-Min Liu; Yeh Chen; Chien-Hung Yu (RNA Biology)
Packaging signals (PSs) of coronaviruses (CoVs) are specific RNA elements recognized by nucleocapsid (N) proteins that direct the selective packaging of genomic RNAs (gRNAs). These signals have been identified in the coding regions of the nonstructural protein 15 (Nsp 15) in CoVs classified under Embecovirus, a subgenus of betacoronaviruses (beta-CoVs). The PSs in other alpha- and beta-CoVs have been proposed to reside in the 5’-proximal regions of gRNAs, supported by comprehensive phylogenetic evidence. However, experimental data remain limited. In this study, we investigated the interactions between Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) 5’-proximal gRNA transcripts and N proteins using electrophoretic mobility shift assays (EMSAs). Our findings revealed that the in vitro synthesized 5’-proximal gRNA transcripts of CoVs can shift from a major conformation to alternative conformations. We also observed that the conformer comprising multiple stem-loops (SLs) is preferentially bound by N proteins. Deletions of the 5’-proximal structural elements of CoV gRNA transcripts, SL1 and SL5a/b/c in particular, were found to promote the formation of alternative conformations. Furthermore, we identified RNA-binding peptides from a pool derived from SARS-CoV N protein. These RNA-interacting peptides were shown to preferentially bind to wild-type SL5a RNA. In addition, our observations of N protein condensate formation in vitro demonstrated that liquid-liquid phase separation (LLPS) of N proteins with CoV-5’-UTR transcripts was influenced by the presence of SL5a/b/c. In conclusion, these results collectively reveal previously uncharacterized binding features between the 5’-proximal transcripts of CoV gRNAs and N proteins.